The Edge Provided by Prostratin Utilization in Reversing Latency and Eradicating Human Immunodeficiency Virus: The Application of Medicinal Plant Extract to Overcome Latency and Eradicate Human Immunodeficiency Virus Completely - Aurelie, Nadine (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2023)
Background: For decades, HIV has caused severe impact toward society by generating vulnerable population. Even though this condition can be kept stabile with antiretroviral usage, other issues including toxicity and resistance emerge due to long term utilization. Therefore, researchers have taken new approach to eradicate HIV infection, which is through shock and kill pace using latency reversal agent. One of the promising candidates is prostratin, compound obtained from medicinal plant extract. Discussion: Aside of reactivating latent HIV-infected cell, prostratin can also prepare related immune system function to combat and eliminate HIV infection, enhancing success chance to obtain full recovery. Combination alongside with other pharmacotherapy agents can further escalate synergist effectivity in shock and kill approach, thus maximizing eradication of HIV infection completely. Conclusion: Therefore, based on the discussion that has been explained above, it can be sum up that prostratin has several advantages compared to other latency reversal agents. Thus, prostratin application might bring one step closer for mankind to annihilate HIV infection completely.